(untitled) (Research, Society and Development, 2024)
Objective: To elucidate the relationship between changes in the intestinal microbiota and weight gain, to describe the composition of the intestinal microbiota in obese individuals and the conditions provided by the intestinal microbiota that favor an increase in the number of adipocytes in these individuals. Methods: Descriptive literature review with bibliographic research carried out in the first half of 2023, using the PubMed and Virtual Health Library (VHL) databases. Articles in English, Portuguese and Spanish were selected, which fit the objectives of this review. The selection was based on the Prisma 2009 protocol, going through the steps: inclusion, eligibility, selection and identification of articles and these were dated from the last 5 years. The descriptors used were “obesity”, “dysbiosis” and ’’intestinal microbiota’’. Results: Changes in the composition of the microbiota after an active and healthy lifestyle are associated with a positive balance between intestinal bacteria: Firmicutes and Bacterioidetes which, in turn, time, showed greater availability of nutrients. Intestinal bacterial diversity is closely linked to more stable individuals, resistant to pathogenic invasions and with no overweight or obesity. Conclusion: The articles studied showed that dysbiosis causes changes in the functioning of the intestinal barrier, generating inflammation, which will contribute to insulin resistance and weight gain. However, more robust studies are needed to continue to reveal the interactions between the intestinal microbiota and obesity.